A Simple Model of Trade, Job Task Offshoring and Social Insurance - Susanna Thede (Lund University, School of Economics and Management, Department of Economics, 2012)
We provide a simple model of trade, job task offshoring and social insurance to identify economic mechanisms through which the interplay between insurance design, (final-goods) trade and job task offshoring determine domestic producer conditions. A skill-abundant home country that may have more productive workers relocates low-skill job tasks to a labor-abundant foreign country. Only the home country provides social insurance to its citizens. Using a simple conceptualization of social insurance targeting the main mechanisms through which insurance design impacts on producer conditions, we formalize productivity, wage-restrictive, compensation, cost-enhancing, cost-redistributive and labor-supply effects of insurance. The home country's labor productivity is superior if the health status of the labor force is improved by health insurance. Generous unemployment insurance trigger binding reservation wages, giving rise to labor-supply effects that lead to a domestic overspecialization of production in trade equilibrium. This tendency is stronger with an insurance design that incorporates a cost-coverage link. Offshoring can introduce, enhance or reduce unemployment in the unskilled labor market depending on a combination of market-related factors and insurance design. In particular, offshoring may give rise to a combination of market-related effects that offset unskilled worker dependency on generous unemployment insurance. An insurance regulation that provides generous unemployment benefits and stipulates cost-redistribution can give rise to a compensation effect through which offshoring generates a high-skill wage reduction.
Keywords: F11; F16; I18; J65; 330; Heckscher-Ohlin; Producer conditions; Labor-market adjustments; Insurance design